Could polyphosphate-accumulating organisms (PAOs) be glycogen-accumulating organisms (GAOs)? - Zhou, Yan; Pijuan, Maite; Zeng, Raymond J.; Lu, Huabing; Yuan, Zhiguo (Water research (Oxford), 2008)
Polyphosphate (poly-P) is known to be a key compound in the metabolism of polyphosphate-accumulating organisms (PAOs). In this study, a sludge highly enriched (80%) in Candidatus Accumulibacter phosphatis (hereafter referred to as Accumulibacter), a widely known PAO, was used to study the ability of these microorganisms to utilize acetate anaerobically under poly-P-limiting conditions. The biomass was subject to several anaerobic and aerobic cycles, during which the poly-P pool of PAOs was gradually emptied by supplying feed deficient in phosphate and washing the biomass at the end of each anaerobic period using media containing no phosphorus. After three cycles, phosphorus was hardly released but PAOs were still able to take up acetate and stored it as polyhydroxyalkanoates (PHA), as demonstrated by post-FISH chemical staining. Glycogen degradation increased substantially, suggesting PAOs were using glycogen as the main energy source. This is a key feature of glycogen-accumulating organisms (GAOs), which are known to compete with PAOs in enhanced biological phosphorus removal (EBPR) systems. The ratios between acetate uptake, polyhydroxybutyrate (PHB) and polyhydroxyvalerate (PHV) production, and glycogen consumption agree well with the anaerobic models previously proposed for GAOs.